The Role of Learning Motivation in Mediating the Influence of Self-Regulated Learning and Peer Social Support on Academic Burnout in Grade XI Boarding School Students at Madrasah Aliyah, Sleman Regency - Ika Nuryana; Daru Wahyuni (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Academic burnout is common among students, especially students who attend boarding schools. Academic burnout is a situation experienced by students due to excessive academic demands and a feeling of no longer being able to accept academic tasks, characterized by emotional and physical exhaustion, cynicism, and decreased academic confidence. This study aims to determine: (1) the effect of self-regulated learning on learning motivation; (2) the effect of peer support on learning motivation; (3) the effect of self-regulated learning on academic burnout; (4) the effect of peer social support on academic burnout; (5) the effect of learning motivation on academic burnout; (6) the effect of self-regulated learning on academic burnout through learning motivation; (7) the effect of peer social support on academic burnout through learning motivation of class XI boarding school students at Madrasah Aliyah, Sleman Regency.This study is a causal associative study with a quantitative approach. The population in this study were 1,023 students of class XI boarding school at Madrasah Aliyah Sleman Regency in 2024 with a sample of 287 students determined by the two-stage random sampling technique. Data collection was carried out using a questionnaire and then processed using path analysis.The results of the study show that: (1) self-regulated learning has a significant positive effect on learning motivation; (2) peer social support has a significant positive effect on learning motivation; (3) self-regulated learning does not have an effect on academic burnout; (4) peer social support has a negative effect on academic burnout; (5) learning motivation has a negative effect on academic burnout; (6) self-regulated learning has a negative effect on academic burnout through learning motivation; (7) peer social support has a negative effect on academic burnout through learning motivation.